Social life cycle assessment indices and indicators to monitor the social implications of wood-based products. (20th January 2018) - Siebert, A.; Bezama, A.; O'Keeffe, S.; Thrän, D.
Abstract: Wood-based products will play a pivotal role in the development of German bioeconomy regions. This transition in production patterns should develop sustainably without negative effects to the environment and society. Therefore, appropriate assessment tools are required to measure and document (un)sustainable aspects. The use of life cycle thinking enables the assessment of sustainability issues relating to such wood-based products. However, life cycle assessment approaches assessing sustainability implications from a regional perspective have not been fully developed yet. A regional perspective is especially required when assessing products' social implications as they are determined by the national and regional socio-economic conditions. In a previous work, we established the "RESPONSA" framework (i.e. a REgional SPecific cONtextualised Social life cycle Assessment) to assess a product's social performance from a regional perspective, directly accounting to the organisations behaviour and therefore providing specific information to support producers' decision-making. This paper focuses on developing a set of social indices and related indicators applicable to wood-based production systems in Germany. This was done in four steps: 1) screening of global, German and wood related sustainability standards; 2) analysis of sLCA case studies; 3) conducting of stakeholder interviews. This allowed the preselection of social aspects relevant to the socio-economic context of interest (i.e. wood-based production chains in German bioeconomy regions). To set up the final set of social indices and indicators, the preselected sets of social aspects, in a fourth step, were further screened regarding their feasible implementation. The established set provides a starting point for assessing and monitoring social implications from wood-based production systems in a regional foreground. Highlights: A set of social indices and indicators was established to assess wood-based production chains. The four development steps are shown. The set enables the assessment of a product's social effects and directly relates to the conduct of associated organisations. The set is part of a context-specific social life cycle assessment framework.